Research on the chemical mechanism in the polyacrylate latex modified cement system. (October 2015) - Wang, Min; Wang, Rumin; Zheng, Shuirong; Farhan, Shameel; Yao, Hao; Jiang, Hao
Abstract: In this paper, the chemical mechanism in the polyacrylate latex modified cement system was investigated by Fourier transform infrared spectra (FT-IR), X-ray photoelectron spectroscopy (XPS), gel permeation chromatography (GPC) and compact pH meter. All results have shown that the chemical reactions in the polyacrylate modified system can be divided into three stages. The hydration reactions of cement can produce large amounts of Ca(OH)2 (calcium hydroxide) and lead the whole system to be alkali-rich and exothermic at the first stage. Subsequently, this environment can do great contributions to the hydrolysis of ester groups in the polyacrylate chains, resulting in the formation of carboxyl groups at the second stage. At the third stage, the final crosslinked network structure of the product was obtained by the reaction between the carboxyl groups in the polyacrylate latex chains and Ca(OH)2 .